Efektifitas Pijat Bayi Sehat dan Pijat Tuina Terhadap Perilaku Makan Anak Balita Usia 1-3 Tahun dengan Gizi Kurang: The Effectiveness of Healthy Baby Massage and Tuina Massage on The Eating Behavior of Toddlers Age 1-3 Years with Malnutrition - Mei Lia Nindya Zulis Windyarti; Anny Martanti; Dyah Ayu Wulandari (Indonesian Journal of Midwifery (IJM), 2023)
Tui Na massage is a more specific massage technique for dealing with feeding difficulties in infants by increasing blood circulation in the spleen and digestion, through a modification of acupuncture without needles, this method uses emphasis on the body's meridian points or energy flow lines so that relative easier to try than acupuncture. Objective: To find out the effectiveness of healthy baby massage and tuina massage on the eating behavior of infants aged 1-3 years with malnutrition. Quasy experimental research with the design of One Group Pre and Post Test Whit Control Group. The population is infants aged 1-3 years with malnutrition in the UPTD Keling 2 Jepara Health Center as many as 108 people. Sampling using purposive sampling as many as 30 respondents for each group. The results of the Paired T-Test showed that there was an effect of Tui na Massage on the Eating Behavior of Children Aged 1-3 Years with Malnourishment at the Keling 2 Health Center, Jepara Regency with a p-value of 0.000< 0. 05. Tui na Massage affects the Eating Attitudes of Children Aged 1-3 Years with Malnourishment. It is recommended that midwives to take advantage of Tui na massage as a non-pharmacological procedure to improve the eating behavior of infants with malnutrition. Abstrak Pijat Tui Na ini ialah tehnik pijat yang lebih khusus buat menangani kesusahan makan pada bayi dengan metode memperlancar peredaran darah pada limpa serta pencernaan, lewat modifikasi dari akupunktur tanpa jarum, metode ini memakai penekanan pada titik meridian badan ataupun garis aliran tenaga sehingga relatif lebih gampang dicoba dibanding akupuntur. Guna Mengetahui Efektifitas Pijat Bayi Sehat serta Pijat Tuina Terhadap Perilaku Makan Anaka Bayi Umur 1- 3 Tahun Dengan Gizi Kurang. Metode: Jenis riset quasy eksperiment dengan desain One Group Pre serta Post Test Whit Control Group. Populasi merupakan bayi umur 1- 3 tahun dengan gizi kurang di UPTD Puskesmas Keling 2 Jepara sebanyak 108 orang. Pengambilan sampel memakai Purposive Sampling sebanyak 30 responden buat tiap kelompoknya. Hasil uji Paired T- Test menampilkan terdapat Ada Pengaruh Pijat Tui na Terhadap Perilaku Makan Anak Usia 1- 3 Tahun dengan Gizi Kurang di Puskesmas Keling 2 Kabupaten Jepara dengan nilai p value 0. 000< 0. 05. Pijat Tui na mempengaruhi terhadap Terhadap Sikap Makan Anak Usia 1- 3 Tahun dengan Gizi Kurang. Dianjurkan kepada tenaga bidan buat memanfaatkan pijat Tui na sebagai prosedur non- farmakologi guna memperbaiki perilaku makan bayi dengan gizi kurang.